Chronic intestinal pseudo-obstruction as the same symptom of various basis - review of literature - Grzegorczyk, Aleksandra; Pachla, Magdalena; Dardzińska, Nicol (Journal of Education, Health and Sport, 2024)
The aim of this work is to discuss the known causes of chronic intestinal pseudo-obstruction. Determining the etiology of the symptoms reported by the patient, such as: abdominal pain, bloating, nausea, constipation, heartburn or regurgitation, the cause of which cannot be clearly identified in imaging tests as mechanical intestinal obstruction, is necessary to implement proper therapy. We distinguished, among others: infections, gene mutations, cancer and paraneoplastic syndromes and autoimmune diseases. This broad range of causes shows the complexity of this disease. Among pathogens, the most common cause are viruses, especially herpesviruses, what is more bacterial infections and gut dysbiosis must be taken under consideration. We found that specific pathway gene mutations can cause obturation symptoms which need extended diagnostic tests. Paraneoplastic syndromes should be examined as a possible etiological factor while looking for the cause of this disease and anticancer treatment can be either a solution for the chronic intestinal pseudo-obstruction symptoms or a cause of them. Lastly we discussed autoimmune diseases as a part of the inflammation problem of the bowel. The goal is to emphasize how important it is to draw attention to the need of looking at the patient and his ailments integrally, which will enable an accurate diagnosis to be made and the appropriate treatment to be effectively selected. We found it very important to think unconventionally with every patient we deal with and what can be done thanks to a great amount of knowledge provided by other doctors.